“Recursos educativos para la transversalidad de género en el ámbito Educativo” - Cuyo Topa, Verónica Alexandra (2021)
In the educational field it is evidenced that teachers have a difficulty in to try topics relating to gender, that causes an ignorance of the theme in the students. It is so, the gender focus contributes to the analysis of contents to generate an equal treatment between men and women. Thus, it is considered pertinent to implement didactic technological material from the gender transversality. The lack of didactic recursion is one of the problems observed since it is taken to the text as a unique resource and origin of information what prevent expanding knowledge in the students. The objective of this research was establish the applicability of the resources and didactic materials in the classroom for practicing transversal values of gender in the students os the Educative Unit “Catorce de Julio” in Latacunga canton. The methodology in this project was based in the qualitative research, in base to the inductive method with descriptive and documental research whose data were obtained through the interview technique applying the interview guide as an instrument to collect information. As a result, is obtained six didactic technologic resources with gender content elaborated by the investigators, which could be used for the educative community. This research contributes to improve the digital abilities, the extension of the recursion and the strategies in the teacher´s labor, in the same way, the practice of values and the integral development of people is encouraged.